Investigation of novel compound 5870, a dipeptidyl peptidase targeted agent, for cancer therapy with specific adaptive immunity - Accetta, Christina. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisor: William Bachovchin.; Committee: Andrew Bohm, John Castellot, Alexei Degterev, and Ralph Isberg.; Keyword: Pharmacology.